2006
DOI: 10.1086/500250
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak ofSerratia marcescensBloodstream Infections Associated With Misuse of Drug Vials in a Surgical Ward

Abstract: We report an outbreak of Serratia marcescens bloodstream infection due to contamination of total parenteral nutrition solution by insulin or poligeline solution when single-use vials were used for multiple doses in a surgical ward. Four patients had severe sepsis, and no patient died. Multidose vials, used either correctly or incorrectly, may be associated with bloodstream infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Recent data showed that all patient of infectious endocarditis due to S. marcescens survived though a combination of antibiotics and early surgical treatment (5). Serratia species has been occasionally recognized as the cause of healthcare-associated bacteremia due to the contamination of blood products (8), cleaning solutions (9), and inadequate sterile techniques with intravenous medication (10,11), however, a recent population-based study of Serratia species infection, including bacteremia in Canada, showed that 65% of infections were community-acquired infections (12) and similarly reports from Australia revealed that 47% of bacteremia episodes were started in the community (13). In the present case, bacteremia due to S. marcescens could have been caused by healthcare-associated infection during the first admission when she received intravenous fluid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data showed that all patient of infectious endocarditis due to S. marcescens survived though a combination of antibiotics and early surgical treatment (5). Serratia species has been occasionally recognized as the cause of healthcare-associated bacteremia due to the contamination of blood products (8), cleaning solutions (9), and inadequate sterile techniques with intravenous medication (10,11), however, a recent population-based study of Serratia species infection, including bacteremia in Canada, showed that 65% of infections were community-acquired infections (12) and similarly reports from Australia revealed that 47% of bacteremia episodes were started in the community (13). In the present case, bacteremia due to S. marcescens could have been caused by healthcare-associated infection during the first admission when she received intravenous fluid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the outbreak we describe, the mortality rate was 0.0%. We speculate that the reason for the absence of mortality was the prompt initiation of effective antibiotic therapy.…”
Section: Discussionmentioning
confidence: 77%
“…6 In the outbreak we describe, the possibility exists that hands contaminated with S marcescens may have contaminated the multidose drug bottles, syringes filled from a vial or the fluid tanks of the nebulizer.…”
Section: Discussionmentioning
confidence: 98%
“…The routine practice at the facility was to use vials designed for single patient use (containing no antibacterial preservative) for multiple patients. Multidose vials have previously been linked to bacterial infections involving contrast material, 10 saline, 7 polygeline or insulin, 11 and narcotics. 12,13 Similar medication use practices and lapses in infection control at other outpatient facilities in New York City and the United States have been linked to numerous outbreaks of hepatitis B and C. 14Y16 After meeting infection control recommendations, the facility was allowed to resume patient care.…”
Section: Discussionmentioning
confidence: 99%